Analysis of the Falling Accidents at the Makkah Holy Mosque Expansion Project - M Basahel, Abdulrahman; M Alqadhi, Esmail (International Journal of Engineering and Technology, 2019)
The current research study aimed to identify the causes of the falling accidents that occurred at the Makkah Holy Mosque Expansion Project in 2014. The categories of falling accidents used in the study were obtained from a record of 429 accidents. Other aspects of falling accidents were also considered in the analysis, including the time of day and the season when the accidents occurred. The analysis results indicated that 42% of the fatal accidents were due to falling and that the plurality of falling accidents during the Holy Mosque project involved falling from a height (27%), followed by falling objects hitting workers (22%) and falling on the same level (10%). More than half of the accidents (55%) occurred during the morning shift.Â Sorting the accident records based on Islamic Arabic (Hijri) calendar months revealed that the accidents had a specific pattern related to those seasons. These results were aided to reduce the falling accidents in the Project. Â Â